Protean Power and Uncertainty: Exploring the Unexpected in World Politics. - KATZENSTEIN, PETER J .; SEYBERT, LUCIA A. (International Studies Quarterly, 2018)
This article introduces the concept of protean power as the basis for a better analysis of unanticipated events in world politics. Protean power is the effect of actors' agility as they adapt in situations of uncertainty. This definition departs from conventional definitions of power, which focus on actors' evolving ability to exercise control in situations of calculable risk and their consequent ability to cause outcomes these actors deem desirable. We argue that this conventional view is overly confining; inclusion of protean power in our analytical models helps us to better account for unexpected change in world politics. Notably, actors respond to shifts between risk and uncertainty, in both context and experience, with affirmation, refusal, improvisation, or innovation. In doing so, they create room for control and protean power as effects, rather than causes, of such practices. However, protean power should not replace control power. These two basic forms of power relate to one another, in a variety of ways, in complex contexts characterized by both risk and uncertainty.